Cyclic microwave assisted synthesis of Sb 2S 3 twin flowers in solutions containing a template and splitting agent - Kavinchan J. (2014)
Antimony sulfide (Sb 2S 3) was successfully synthesized from antimony chloride (SbCl 3) and sodium thiosulfate (Na 2S 2O 3) in ethylene glycol (EG) containing different contents of cetyltrimethylammonium bromide (CTAB) as a template and splitting agent by the 600 W cyclic microwave radiation (CMR). X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy and photoluminescence (PL) spectroscopy revealed the presence of only orthorhombic Sb 2S 3 phase in the shape of twin flowers of single crystalline square nanorod petals, growing along the [001] direction, including the vibration peaks that were in accordance with those of the stibnite with the 435 nm violet wavelength emission peaks.